Spanish Validation of the Self-Reported Antisocial Behavior Questionnaire and Comparison of Adolescent Antisocial Behaviors Between Pittsburgh and Cordoba - Espejo-Siles, Raquel (Crime & delinquency, 2025)
Antisocial behavior is a worldwide problem that negatively affects individuals and societies, and it is influenced by contextual factors. The study of how antisocial behavior changes through time frames and among countries provides information of the extent to which the environment influences this problem, which could help to develop more accurate prevention programs. Cross-national studies require instruments with good psychometric properties, validated in different cultures and languages. Thus, the aim of this study was to validate the Spanish version of the Self-Reported Antisocial Behavior Questionnaire, and to analyze whether there are differences in reported antisocial behavior between pre-adolescents in Pittsburgh, North America (1988) and Cordoba, Spain (2017). The sample included 1,483 Cordoba students of whom 203 were comparable in age to 868 Pittsburgh boys. Results showed that the Spanish version of the Self-Reported Antisocial Behavior Questionnaire had excellent psychometric properties, and that there were some similarities and differences in antisocial behaviors reported by the samples from Pittsburgh and Cordoba. Results are discussed according to time frames and environmental influences of the samples. Implications for policy and practice are discussed.